A quinoline-based fluorescent probe for selective detection and real-time monitoring of copper ions – a differential colorimetric approach. Issue 12 (7th November 2019) - Farhi, Atika; Firdaus, Farha; Saeed, Haris; Mujeeb, Anzar; Shakir, Mohammad; Owais, Mohammad
Abstract : A quinoline moiety was used as a building block for designing a probe for the selective detection of copper ions in a partially aqueous medium. Abstract : A quinoline moiety was used as a building block for designing a probe for the selective detection of copper ions in a partially aqueous medium. We have developed a molecular sensing system which gives insight into the complex physiological and redox aspects of labile copper. The probe provides a colorimetric approach for distinguishing cuprous and cupric ions along with their simultaneous discrimination from other metal ions in the visible range of the spectrum. The chemosensor showed a remarkable fluorescence enhancement along with a significant bathochromic shift of about 35 nm. The detection limit of the probe was found to be 1.03 μM which is optimally favorable to be applied in real-time monitoring. Fabrication of paper strips with the probe was done to detect the presence of cuprous ions in the real sample. The value of the binding constant (1.37 × 10 4 M −1 ) suggests stable complex formation between the metal ion and the sensing probe. The photoluminescence and structural aspects of the chemosensor were characterized by using fluorescence, absorption, ESI-MS, and 1 H NMR spectroscopy. Furthermore, the cytotoxic nature and bioimaging properties of the probe were interpreted in vitro on RAW 264.7 macrophage cell lines and peripheral blood mononuclear cells (PBMCs) respectively.